Late Complications of Acute Pancreatitis: Diagnosis and Treatment - Daniel T. Marine, Bailey V. Cabrera, William S. Jenkins, Henry M. Haley (Academic Journal of Clinicians, 2024)
"Objective: This study aimed to discuss the diagnosis and treatment of late complications that may arise following an episode of acute pancreatitis. Methods: A comprehensive review of the literature was conducted to identify studies and guidelines related to the late complications of acute pancreatitis. The focus was on the diagnosis and treatment strategies for these complications. Key aspects such as clinical presentation, diagnostic modalities, and therapeutic interventions were analyzed. Results: Late complications of acute pancreatitis encompass a range of conditions, including pancreatic pseudocysts, pancreatic necrosis, pancreatic duct strictures, and pancreatic endocrine and exocrine insufficiency. Diagnosis typically involves a combination of clinical evaluation, imaging studies (e.g., CT scan, MRI), and laboratory tests. Treatment options vary depending on the specific complication but may include minimally invasive techniques (e.g., endoscopic drainage, percutaneous drainage), surgical intervention, or medical management. Conclusion: Timely diagnosis and appropriate treatment are crucial in managing the late complications of acute pancreatitis. A multidisciplinary approach involving gastroenterologists, interventional radiologists, and surgeons is often necessary to optimize patient outcomes. Early intervention and individualized treatment strategies can help mitigate the long-term sequelae associated with these complications. "